Arithmetic modelling - a link between discrete-time systems and binary process control - Franke, Dieter (Zielona Góra: Uniwersytet Zielonogórski)
The paper addresses finite state machines which provide suitable mathematical models for discrete-event dynamical systems. Boolean automata are of particular interest. In contrast to the classical automata theory, an arithmetic representation of Boolean functions is used based on multilinear polynomials.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka